Value of discrimination indices in screening of beta thalassaemia trait - Nesa, Ayatun; Munir, Sk Farhad; Sultana, Tuhin; Rahman, Md Quddusur; Shomik, Mohammed Shohel; Ahmed, AN Nashimuddin (Bangladesh Journal of Pathology, 2010)
Key words: Beta thalassaemia; discrimination indices DOI: 10.3329/bjpath.v25i1.4126 Bangladesh J Pathol 25(1): 14-17